Application of Traditional Medical Ideas to Geriatric Syndrome. (15th July 2014) - Seki, Takashi; Takayama, Shin; Watanabe, Masashi; Tsuruoka, Noriko; Matsunaga, Tadao; Haga, Yoichi; Okajima, Junnosuke; Komiya, Atsuki; Maruyama, Shigenao; Meguro, Kenichi
Abstract : Background . Japan is a superaging society, with the percentage of persons aged >65 years increasing year after year. Traditional medicine (TM) for elderly has been practiced worldwide for thousands of years. Treatment methods for aspiration pneumonia, gait disorder, glaucoma, and bowel symptoms have been developed. The ideas of acupuncture, moxibustion, and herbal medicine have been implemented in modern medical settings, and medical devices using heat transfer engineering and nanotechnology have been developed. An ultrasound scanner can be used for the evaluation of effects and indications for these therapeutic measures. Objectives . To review published literature and our studies that evaluated medical treatments for the elderly on the basis of ideas of TM. Search Methods . We searched Pubmed, Scopus, and reference lists of relevant clinical trials. Authors' Conclusions . Many studies were found. But there are insufficient data on the effects of traditional medical therapies and further research is needed. TM therapies vary widely and studies of these therapies that ascertain practical application are essential for the utilization of ideas of TM in modern medicine. Moreover, to verify practical application, a quantitative evaluation index is necessary. Nonetheless, modalities using ideas of TM may be promising treatments for some diseases in the elderly.